Abnormal geophysical and seismotectonic processes observed during the period of preparation and development of the earthquake with a magnetude of 8,8 Maule 2010 (Chile) - Sobisevich, L.E.; Starostenko, V.I.; Rogozhyn, E.A.; Lutikov, A.I.; Sobisevich, A.L.; Kanonidi, K.H.; Kendzera, A.V.; Orlyuk, M.I. (Geofizicheskiy Zhurnal, 2016)
Focal zone, basic shock, jerking of strongest aftershocks and progress of seismic energy release during the aftershock process of the earthquake Maule 27.02.2010 (M W =8,8) in Chile have been analyzed. Macroseismic manifestations, tectonic position of the focus and reconstruction of acting plane position in the focus have been considered. Geophysical treatment of anomalous gravimagnetic disturbances and seismic precursors induced in variations of magnetic field and geoacoustic fields of the Earth during preparation of the basic shock and of three strongest iterative shocks on March 11 —16 2010 has been done for the first time. It has been shown that application of present-day cosmic observations, which allow to analyze gravity disturbances (so far only coseismic), reflected on the Earth’s surface makes possible to consider the precursors of seismic shocks of the arthquake Maule and other seismic events in a new way. Long-, middle- and short-term approaches to prognostication of strong seismic events both on land and sea have been stated